ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL CERITA MATERI BENTUK ALJABAR - Shinta Oktavira; Dani Firmansyah (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
This study aims to describe errors that occur when solving story problems in algebraic form. This study uses a qualitative descriptive method. The subjects in this study used a limited sample of students of SMP Negeri 4 Tambun Utara, as many as 18.92% of students from class VII.5 who had filled out the questions given. The technique used to collect this data is through the answers to the description questions in the form of four questions in the form of story questions and then analyzed by the researchers to see what mistakes students might make when solving the story questions in the algebraic form contained in the student's answers. Through the results of the research and discussion, the researcher concluded that the errors that occurred when solving the questions were as follows: all information and problems in the questions were not rewritten briefly and did not understand the problems in the questions, determined the method of solving that was not appropriate, the existing data was not used during the process. completion, and did not write down the final conclusion that indicated that he had answered the problem in the problem.